In vitro evaluation of phytochemical loaded electrospun gelatin nanofibers for application in bone and cartilage tissue engineering. (25th October 2018) - Venugopal, Elakkiya; Rajeswaran, Narmadha; Sahanand, K Santosh; Bhattacharyya, Amitava; Rajendran, Selvakumar
Abstract: Wattakaka volubilis, a medicinal plant, is known to exhibit various potential health benefits and has traditionally been used in Ayurveda for various medicinal applications. In the present study, phytochemicals hexadecanoic acid, octadecanoic acid and N, N-Diisopropyl(2, 2, 3, 3, 3-pentafluoropropyl)amine isolated from W. volubilis leaf extract were co-electrospun with gelatin nanofibers for meniscus and osteoblast cell attachment and proliferation. The electrospun nanofibers were characterized using suitable techniques such as a scanning electron microscope and Fourier transform infrared spectroscopy. The mechanical property of electrospun gelatin nanofibers and phytochemicals incorporated gelatin nanofibers were tensile tested. Both the control and phytochemical loaded nanofiber exhibited a similar stress–strain trend. The average diameter of the control and phytocompound loaded gelatin nanofiber was found to be 300 ± 5.5 nm and 483 ± 12 nm, respectively. The rate of biodegradation of the control and phytochemical loaded nanofiber was analyzed in a simulated body fluid. The cell attachment and proliferation were monitored using a fluorescence microscope after appropriate staining. The cell viability, DNA content, extracellular secretion confirmed that the phytocompound loaded gelatin nanofibers were non-toxic and enhanced the meniscus and osteoblast cell growth and proliferation. This phytocompound loaded gelatin matrix may be used as a potential scaffold for cartilage and bone tissue engineering applications.